2018
DOI: 10.1002/1878-0261.12354
|View full text |Cite
|
Sign up to set email alerts
|

A patient‐derived explant (PDE) model of hormone‐dependent cancer

Abstract: Breast and prostate cancer research to date has largely been predicated on the use of cell lines in vitro or in vivo. These limitations have led to the development of more clinically relevant models, such as organoids or murine xenografts that utilize patient‐derived material; however, issues related to low take rate, long duration of establishment, and the associated costs constrain use of these models. This study demonstrates that ex vivo culture of freshly resected breast and prostate tumor specimens obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 48 publications
0
98
0
1
Order By: Relevance
“…21,23,28,29 As reported in these studies, maintenance of prostate or PCa tissue slices for a week could be achieved, but conservation of tissue structure and functionality was not always comprehensively reported with extensive variability in tissue origin and evaluation in the different studies. Application of the ex vivo culture system for drug testing was only reported in a few studies, describing reduced cell proliferation in response to genistein, 29 cisplatin combined with a BcL-2 antagonist, 30 heat shock protein 90 inhibitors 28 PARP-1 inhibitors, 31 and most recently published studies with bicalutamide 32 and docetaxel. 33 However detailed cell cycle progression (proliferation) of the tumor cells was not investigated, making direct comparison to our studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…21,23,28,29 As reported in these studies, maintenance of prostate or PCa tissue slices for a week could be achieved, but conservation of tissue structure and functionality was not always comprehensively reported with extensive variability in tissue origin and evaluation in the different studies. Application of the ex vivo culture system for drug testing was only reported in a few studies, describing reduced cell proliferation in response to genistein, 29 cisplatin combined with a BcL-2 antagonist, 30 heat shock protein 90 inhibitors 28 PARP-1 inhibitors, 31 and most recently published studies with bicalutamide 32 and docetaxel. 33 However detailed cell cycle progression (proliferation) of the tumor cells was not investigated, making direct comparison to our studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 In the breast cancer study, PDE responses to the targeted therapy TRAIL were found to be more consistent with clinical trial data than 2D tumour model systems. 80,84 The gelatine-sponge approach has proved successful for the culture of explants derived from breast and prostate tumours, 85 and has been applied to the testing of novel anti-cancer agents, 66,67,86,87 development of biomarkers 87,88 and for monitoring changes in the tumour microenvironment. 89 In these studies, the PDE approach contributed important information to show the effect of the PARP inhibitor ABT888 in suppressing tumour cell proliferation in human prostate cancers 86 and the effect of progesterone in inhibiting the proliferation of the oestrogenmediated growth of ERα + breast cancers.…”
Section: Recent Advances In Pde-based Platformsmentioning
confidence: 99%
“…4a). PDXDE models have been shown to accurately predict patient-specific responses to multiple drugs and to mimic in vivo results in breast cancer 44,45 . We first established the appropriate culture conditions to maintain TNBC PDXDEs.…”
Section: Pharmacological Inhibition Of Glut1 Impedes Tnbc Cancer Growmentioning
confidence: 99%